On the Need of Conviviality: Experiences of Religious Diversity of Nordic Youth - Vähäkangas, Auli (Exchange, 2018)
This article studies young people’s experiences of religious diversity in two Nordic localities in Finland and in Norway. In the Nordic discourse, the concept of conviviality gained importance through the lwf’s policy document Seeking Conviviality in 2013. Haugen’s three “Rs”, respect, relationality and reciprocity will be used as a starting point for the analysis of the experiences of young people. The aim of the study is to understand how young people experience religious diversity and what these experiences can contribute to Haugen’s reformulation of conviviality. The results show that conviviality tends to be more easily discussed than practised. They indicate that living in the same neighbourhood with youth from other religious traditions helps to face religious diversity but that this coexistence does not in itself generate reciprocity. Rather, in order to really live together there is a need to get to know each other’s practices and values more deeply.